The Birth Rate of Low-Mass X-Ray Binaries - Winardi Sutantyo (Jurnal Matematika & Sains, 2003)
The evolutionary history and formation of low-mass X-ray binaries is considered. Various effects during their formation process are taken into account. Special emphasis is given to the common envelope evolution, the effect of an asymmetry in the supernova and the impact of the supernova shell on the companion star. Assuming a kick velocity between zero and 500 km s-1, the derived birthrate for low-mass X-ray binaries from the model computations is reconciable with estimated from the observed galactic population of O(100) and lifetime of O(108,7) yr if the common envelope efficiency is low (Î± CE â¤ 1,5). In this case, the derived birth rate depends only weakly on the kick velocity. Higher Î± CE results in a higher birthrate unless the kick velocity is also high (â¥ 500 km s-1), which is incompatible with the observed mean velocity of pulsars. We conclude that the standard scenario produces a birthrate for low-mass X-ray binaries which is reconciable with the observations if Î± CE is low and this is valid for any kick velocity between zero and 500 km s-1.